Design, synthesis and biological evaluation of fused naphthofuro[3,2-c] quinoline-6,7,12-triones and pyrano[3,2-c]quinoline-6,7,8,13-tetraones derivatives as ERK inhibitors with efficacy in BRAF-mutant melanoma - Aly, Ashraf A.; Garvalov, Boyan K. (Bioorganic chemistry, 2019)
Approximately 60% of human cancers exhibit enhanced activity of ERK1 and ERK2, reflecting their multiple roles in tumor initiation and progression. Acquired drug resistance, especially mechanisms associated with the reactivation of the MAPK (RAF/MEK/ERK) pathway represent a major challenge to current treatments of melanoma and several other cancers. Recently, targeting ERK has evolved as a potentially attractive strategy to overcome this resistance. Herein, we report the design and synthesis of novel series of fused naphthofuro[3,2-c]quinoline-6,7,12-triones 3a-f and pyrano[3,2-c]quinoline-6,7,8,13-tetraones 5a,b and 6, as potential ERK inhibitors. New inhibitors were synthesized and identified by different spectroscopic techniques and X-ray crystallography. They were evaluated for their ability to inhibit ERK1/2 in an in vitro radioactive kinase assay. 3b and 6 inhibited ERK1 with IC50s of 0.5 and 0.19µM, and inhibited ERK2 with IC50s of 0.6 and 0.16µM respectively. Kinetic mechanism studies revealed that the inhibitors are ATP-competitive inhibitors where 6 inhibited ERK2 with a Ki of 0.09µM. Six of the new inhibitors were tested for their in vitro anticancer activity against the NCI-60 panel of tumor cell lines. Compound 3b and 6 were the most potent against most of the human tumor cell lines tested. Moreover, 3b and 6 inhibited the proliferation of the BRAF mutant A375 melanoma cells with IC50s of 3.7 and 0.13µM, respectively. In addition, they suppressed anchorage-dependent colony formation. Treatment of the A375 cell line with 3b and 6 inhibited the phosphorylation of ERK substrates p-90RSK and ELK-1 and induced apoptosis in a dose dependent manner. Finally, a molecular docking study showed the potential binding mode of 3b and 6 within the ATP catalytic binding site of ERK2.
Gesehen am 10.04.2019
Available online 23 October 2018